Treatment of intestinal helminthiasis: mebendazole only or mebendazole-pyrantel pamoate? - Wisman Dalimunthe; Charles Siregar; Munar Lubis; Syahril Pasaribu; Chairuddin P. Lubis (Paediatrica Indonesiana, 2007)
Background Although intestinal helminthiasis causes highmorbidity and has a negative impact on children’s growth anddevelopment, the efficacy of antihelmintics for multiplehelminthiasis in mass treatment is still doubtful.Objective To compare the efficacy of single dose mebendazoleand a combination of pyrantel pamoate and mebendazole for thetreatment of multiple infections due to Ascaris lumbricoides,hookworm, and Trichuris trichiura.Methods Subjects were elementary school students in Suka Village,Tiga Panah subdistrict, North Sumatera. They were randomizedto either receive mebendazole (M Group) or mebendazole-pyrantel pamoate group (MP Group). Stool examinations wereperfomed on each subjects on day 7, 14, 21, and 28 after treatment.Analyses were perfomed by using chi-squared and Mann-WhitneyU tests.Results The prevalence of intestinal helminthiasis was 95.4%. T.trichiura (88.7%) was the most common cause of infection followedby A. lumbricoides (79.5%), and hookworm (3.1%). Two hundredthirty nine (76.8%) children had multiple infections. Althoughthe egg reduction rate of intestinal helminthiasis in thecombination group was faster than that of the mebendazole group,there was no significant difference in the cure rate of both groups.Conclusion A single dose of mebendazole is preferred for masstreatment of multiple intestinal helminthiasis infections.